Application Of Ma'ani Knowledge To Improve Students' Rhetorical Analysis Competence And Contextual Comprehension - Hasyim Asyari; Akh Setyo Muzakki; Husniyatus Salamah Zainiyati; Nasaruddin Idris Jauhar; Nahla Ibrahim ElJack; Amar bin Muhammad Edi bin Ahmed (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This research aims to uncover the effectiveness, strategies, and learning models based on the application of ma'ani knowledge in improving students' rhetorical analysis and contextual understanding competencies in learning Arabic. The method used is descriptive qualitative with a library research approach, data analysis in the form of content analysis, and data validity through source triangulation. The results of the study show that the application of ma'ani science includes the analysis of khabar–insyā', taqdim–ta'khir, ta'rīf–tankīr, faṣl–waṣl, ījāz–iṭnāb, as well as the pattern of musnad–musnad ilayh and muta'allaq al-fi'l in Surah Al-Fātiḥah can be used as a learning basis to improve students' rhetorical analysis skills and contextual understanding. The learning strategy based on knowledge indicators helps students identify the focus of meaning, interpret rhetorical intensity, and understand the linguistic structure of the Qur'anic texts in depth and systematically, while enriching their academic, spiritual, and linguistic understanding.